A New Bretton Woods? - Rajan, Raghuram G. (World Bank, Washington, DC, 2017)
The Bretton Woods sisters, the International Bank for Reconstruction and Development (henceforth the World Bank) and the International Monetary Fund (IMF), were set up in 1944. The original purpose of the former was to help post-Second World War reconstruction; the purpose of the latter was to help revive global trade while averting the 'beggar-thy-neighbor' exchange rate policies that characterized the interwar years. Over the years, the World Bank has refocused on helping poor countries grow while the IMF broadly attempts to foster country policies that ensure macroeconomic stability and limit adverse spillovers to the rest of the world. While these roles still remain, their nature has changed somewhat. In particular, given the development of financial markets around the world, the primary role of these institutions has moved to shaping, guiding, supplementing, and stabilizing the flow of private finance rather than substituting fully for it. This paper focuses on the new ways multilateral institutions may have to perform old tasks, as well as the ways they could perform new tasks such as slowing climate change. Critical to their transformation will be the attitudes of the countries that play the largest role in their governance, as well as reform of the governance process itself.